2020
DOI: 10.3390/en13154023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Energy Storage from Photovoltaic Installations in Poland Using Batteries or Hydrogen

Abstract: This paper presents a series of economic efficiency studies comparing three different investment variants: without energy storage, with energy stored in batteries and hydrogen installation with a PEM fuel cell stack for a location in Poland. To reach a target, the current solar potential in Poland, the photovoltaic (PV) productivity, the capacity of the energy storage in batteries as well as the size of the hydrogen production system were calculated. The solar potential was determined using archival meteorolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Renewable energy is a response to the most pressing socio-economic challenges and climate change. It is important to increase investments in renewable energy [66].…”
Section: International Conditions Shaping the Development Of Renewable Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Renewable energy is a response to the most pressing socio-economic challenges and climate change. It is important to increase investments in renewable energy [66].…”
Section: International Conditions Shaping the Development Of Renewable Energymentioning
confidence: 99%
“…The actions taken indicate a technological gap between developed and developing countries, which could be widened. The development of renewable energy sources becomes crucial [66].…”
Section: International Conditions Shaping the Development Of Renewable Energymentioning
confidence: 99%
“…Photovoltaic technology, also known as solar-electric technology, converts sunlight directly into electrical energy (Oji et al, 2012). A photovoltaic system has a sense of balance to it, which includes component mounting structures, power equipment coordination, tracing structures, concentrator systems, and regenerating storage devices (Bernard et al, 2020). Solar electric conversion can, of course, be done on a small scale for standalone systems or on a large scale that is connected to the national grid (USCCTP, 2005).…”
Section: Solar Power Potential In Nigeriamentioning
confidence: 99%
“…20 Besides, a similar study concluded that electricity storage in hydrogen is more advantageous than in batteries due to the smaller investment outlays. 21 Most recent works on MatLab/Simulink of solar PV-tohydrogen including or not a battery can be found in Ismail et al 22 Most of these research concluded that the experimental and simulation results matched significantly. In the literature, global solar radiation is used in the simulation, but in this study, the direct solar radiation and albedo is accounted through Hybrid Optimization of Multiple Energy Resources (HOMER) data, and it is used with the PV system model to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%